Demonstration Learning Method Assisted by Hand Puppet Media Improves Children's Language and Social-Emotional Skills - Luh Komang Yuniari; Desak Putu Parmiti; I Gede Astawan (Universitas Pendidikan Ganesha, 2024)
During learning, children feel bored and shy when meeting new people, so they need to be adequately stimulated to support the child's social-emotional development. This research analyzes the demonstration learning method assisted by hand puppets on children's language and social-emotional abilities. This type of research is Quasi-Experimental Design (quasi-experiment). The research design used was a posttest-only control group design. In this study, the population was the total number of Kindergarten B children, totaling 185 children. The sample selection technique in this research was random sampling with a sample size of 65 children. The data collection method uses observation and questionnaire sheets. Inferential statistical analysis is an analysis used to test research hypotheses. The research results show that the Demonstration Learning Method Assisted by Hand Puppet Media can influence children's language and social-emotional abilities. The research results show differences in the language and social-emotional abilities of children who follow the demonstration learning method assisted by hand puppet media and those taught using the lecture method. It was concluded that the Demonstration Learning Method Assisted by Hand Puppet Media could improve Kindergarten B children's language and social-emotional skills.